PERLINDUNGAN HUKUM UNTUK WISATAWAN MUSLIM DI INDONESIA BERDASARKAN PERATURAN PERUNDANG UNDANGAN DAN HUKUM ISLAM - Rully Putra Jaya; Hidayat (JOURNAL OF LAW AND NATION, 2023)
The results of this study explained the following: First, Government laws and Regulations regarding tourism are considered to be able to protect tourists in general but have not regulated and protected the rights of muslim tourists specifically. Second, law number 8 0f 1999 concerning consumer protection is considered to protect tourists. However, when it is used for seeking justice through the courts, it needs to be interpreted differently in muslim tourist disputes, According to Arcticle 46, the term general courts is interpreted as religios coursts. Third, Government Laws and regulations regarding halal product assurances are very effective in efforts to provide security and comfort in terms of consumptions of muslim tourists. Fourth, the current local government regulation is an alternative positive regulation that is applicable to halal tourism. Fifth, The Fatwa Of National Sharia Board (DSN) nomber 108 0f 2016 of concerning halal tourism that is used a guideline for halal tourism regulations is still limited, as it only applies to regions that apply local governmant regulations on halal tourism. Sixth, The Fatwa Of DSN-MUI does not have binding legal force until it is adopted to the Government Laws And Regulations